In vivo metabolism of alpha-tocopherol in lipoproteins and liver: studies on rabbits in response to acute cholesterol loading - Fragoso, Yara Dadalti (1998)
OBJECTIVE: To investigate the transport of alpha-tocopherol in lipoproteins of rabbits under normal diet and under acute loading of cholesterol. DESIGN: Two New Zealand White rabbits were fed 14C-alpha-tocopherol acetate in a single oral dose and the recovery of radiolabel in lipoproteins and plasma was monitored. Low density lipoprotein (LDL) from these animals was obtained and labeled with [3H] cholesteryl ester. Three other rabbits were injected with this double-labeled LDL in the native form; while three other animals received this LDL in the acetylated form. RESULTS: Plasma clearance, liver uptake and levels of radiolabel in high density lipoprotein (HDL) of animals injected with 14C[3H]acetyl LDL were significantly higher than those in animals injected with 14C[3H]native LDL. Larger particles of HDL, rich in apolipoprotein E (apoE) carried significantly higher levels of both labels in rabbits injected with acetylated LDL. CONCLUSION: These results provide evidence for in vivo mechanisms of "reverse alpha-tocopherol transport", analogous to "reverse cholesterol transport".